Effects of Liming on Forage Availability and Nutrient Content in a Forest Impacted by Acid Rain - Pabian, Sarah E.; Ermer, Nathan M.; Tzilkowski, Walter M.; Brittingham, Margaret C. (PLOS ONE, 2012)
Acidic deposition and subsequent forest soil acidification and nutrient depletion can affect negatively the growth, health and nutrient content of vegetation, potentially limiting the availability and nutrient content of forage for white-tailed deer (Odocoileus virginianus) and other forest herbivores. Liming is a mitigation technique that can be used to restore forest health in acidified areas, but little is known about how it affects the growth or nutrient content of deer forage. We examined the effects of dolomitic limestone application on the growth and chemical composition of understory plants in an acidified forest in central Pennsylvania, with a focus on vegetative groups included as white-tailed deer forage. We used a Before-After-Control-Impact study design with observations 1 year before liming and up to 5 years post-liming on 2 treated and 2 untreated 100-ha sites. Before liming, forage availability and several nutrients were below levels considered optimal for white-tailed deer, and many vegetative characteristics were related to soil chemistry. We observed a positive effect of liming on forb biomass, with a 2.7 fold increase on limed sites, but no biomass response in other vegetation groups. We observed positive effects of liming on calcium and magnesium content and negative effects on aluminum and manganese content of several plant groups. Responses to liming by forbs and plant nutrients show promise for improving vegetation health and forage quality and quantity for deer.